Quality at work : a personal guide to professional standards - Bone, Diane (Crisp Pub. Menlo ParkUS, 1989)
Defines quality and discusses the intangables of quality, viz. commitment, competence and communication. Examines personal quality standards, and discusses their relation to the work situation. Gives guidelines for setting quality goals based on the organization's work purpose. Provides a seven-step plan for establishing perfection standards.